Impact of a pre-school milk on nutrient status, intake and growth in children aged 3–5 years old: a 16-week randomized, parallel clinical study - Estorninos, Elvira; Lawenko, Rachel B.; Lebumfacil, Jowena D.; Posecion, J. Edgar Winston C.; Delos Reyes, Veron Catrisse; Petit-Jean, Alison; Egli, Delphine; Tanda, Keith V.; Agdeppa, Imelda (Frontiers in Nutrition, 2025)
BackgroundRecent research suggests there is an increasing burden of malnutrition in the Philippines due to insufficient or deficient consumption of micronutrients and energy. This open-label, randomized, prospective clinical study examines the impact of the consumption of a pre-school milk for young children on micronutrient status, nutritional intake, and growth.MethodsHealthy, singleton, term Filipino children aged 3–4.5 years were randomized to receive a fortified pre-school milk product (n = 56; INT) or consume their habitual diet (n = 55; CTRL). The primary outcome was nutritional status of key micronutrients, including vitamins A, D, E, and zinc. Micronutrient status was assessed at baseline and after 16 weeks of intervention. Secondary endpoints in this study included anthropometric measurements, nutrient intakes, developmental milestones, incidence of illnesses, and medication use.ResultsMean age at baseline was approximately 44 months old. Almost all children (98%) were consuming fortified milk before being enrolled in the study. The primary outcome, micronutrient status did not significantly differ between INT and CTRL at baseline or after 16 weeks (p > 0.05). Mean nutrient intakes were higher in INT compared to CTRL and closer to the recommendations. A significant increases in weight and height from baseline to endline were observed in both groups. After 16 weeks, mean weight and BMI were significantly higher in INT vs. CTRL (p < 0.005) with mean weight-for-age, height-for-age and BMI-for-age z-scores tracked closer to the WHO median for the INT group. The total number of sick days was 162 in INT vs. 181 in CTRL.ConclusionIn this randomized, parallel clinical study, children consuming a pre-school milk for 16 weeks had improved nutrient intakes and increased rate of growth compared to a group of children consuming their habitual diet.